A autocomposição como política pública de tratamento de conflitos administrativos na UFG a partir de 2019: a CPRAC – Câmara de Prevenção e Resolução Administrativa de Conflitos - Pires, Rodrigo Corrêa (2020)
The present work approaches a new proposal of Public Administration action, moving away from the traditional hierarchical model and adopting a dialogical posture, promoting the consensual resolution of conflicts. The theoretical framework starts from the analysis and discussion of Game Theory, an articulation that served as a basis for the Harvard Negotiation Program which, although established on a quantitative view of the use of conflict self-composition, is based on conflict negotiation procedure under a principiological bias, where the search for an agreement that pleases both parties becomes its main object. The state's duty to promote good administration is also addressed by correlating the institute with obtaining satisfactory levels of efficiency from the perspective of the unavailability of the public interest and the promotion of public policy of consensus. In this sense, the law from the conflict will be analyzed, moving away from the heterocompositive model based on the “culture of the sentence” and moving towards the “culture of dialogue”, both in the Judiciary and in Public Administration. In this area, the practical case of the Federal University of Goiás will be analyzed, which instituted a structure aimed at the administrative resolution of conflicts based on conflict mediation techniques.